Clinical researchThe influence of pre-emptive analgesia on postoperative analgesia and its objective evaluation - Fricova, Jitka; Vejražka, Martin; Stopka, Pavel; Krizova, Jana; Běláček, Jaromír; Rokyta, Richard (Archives of Medical Science, 2010)
Introduction : The evaluation of pain intensity is still a subject of research. Mostly psychological evaluations are used. We started to conduct biochemical evaluation in animal experiments. Now we present biochemical evaluation in postoperative pain in man. Material and methods : In 67 patients herniotomy was done. For pre-emptive analgesia morphine and pethidine were used and the following indicators were measured: visual analogue scale (VAS), measurement of lipid spectra, saccharides and proteins, thioredoxin, super-oxide dismutase (SOD), glutathione peroxidase (GPx) and NAD(P)H-oxidase (NOX), and free radicals using electron paramagnetic resonance (EPR). Blood samples were taken and tested: before pre-medication and intervention, 4 h after and 24 h after intervention. Results : Free radicals (FR) increased in individual samples during the postoperative course in pethidine and without pre-medication. After application of morphine the FR were insignificantly reduced. Statistically significant differences were found in albumin, prealbumin, apolipoprotein A, total cholesterol, atherosclerotic index, CRP, glucose, and thioredoxin (p  0.001). A greater difference was seen in VAS values between morphine and pethidine premedications (p  0.001). Conclusions : It was proved that the biochemical markers of lipid, protein and saccharide metabolisms and free radicals as well as singlet oxygen can serve as very good indicators of the intensity of pain and nociception. In patients it was proved that pre-emptive analgesia plays an important role in reducing the intensity of postoperative pain. From the three modalities of pre-emptive analgesia morphine represents the best solution.